STUDY OF ADVERSE DRUG REACTIONS OF LINEZOLID IN DRUG RESISTANT TUBERCULOSIS PATIENTS - Susilo, Rinto; Sundhani, Elza; Setyaningsih, Indah; Retnaningsih, Ririn; Nurjanah, Ucu; Endang Ayu Prihatini, Nok (Jurnal Farmasi Sains dan Praktis, 2025)
The estimated number of DR TB patients in Indonesia is increasing. High adverse drug reactions have the potential to affect the success of DR TB patient treatment. Linezolid is one of the drugs in combination with DR TB therapy that has the potential to cause adverse drug reactions in the form of hematological disorders and visual impairment. This study aims to determine the incidence of Linezolid ADRs, including the incidence, severity, and risk factors associated with the occurrence of ADRs. This type of study is observational with a cross-sectional design conducted retrospectively in DR TB patients at the lung clinic of Hospital 'X" and Hospital "Y" in Indonesia. The results of the study showed that the incidence of ADRs suspected of Linezolid that met the criteria was 70 patients out of a total of 215. The most common type of ADRs was hematological disorders at 89%, the rest were visual impairment. The type of regimen and type of ADRs correlate with the severity of ADRs. It is necessary to monitor drug levels in the blood in order to monitor and prevent the potential for more severe ADRs so that therapy can be individualized.